2009
DOI: 10.1016/j.nurt.2009.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell-Derived Neural Precursor Grafts for Treatment of Temporal Lobe Epilepsy

Abstract: Summary:Complex partial seizures arising from mesial temporal lobe structures are a defining feature of mesial temporal lobe epilepsy (TLE). For many TLE patients, there is an initial traumatic head injury that is the precipitating cause of epilepsy. Severe TLE can be associated with neuropathological changes, including hippocampal sclerosis, neurodegeneration in the dentate gyrus, and extensive reorganization of hippocampal circuits. Learning disabilities and psychiatric conditions may also occur in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 120 publications
0
34
0
Order By: Relevance
“…Rigorous analyses of anti-epileptogenic effects of diverse donor cell types that are easily accessible will be needed in IPI models of TLE. The donor cells may include hippocampal precursor cells, GABA-ergic progenitors, and NSCs obtained from diverse sources, including the human ES cells and the human iPS cells, as the technology for generating such cells from these sources is currently being developed [93,94]. The use of such cells would also prevent the dependency on human fetal derived cells, which are difficult to obtain in sufficient quantities required for grafting, and their use is also restrained because of ethical concerns [25].…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous analyses of anti-epileptogenic effects of diverse donor cell types that are easily accessible will be needed in IPI models of TLE. The donor cells may include hippocampal precursor cells, GABA-ergic progenitors, and NSCs obtained from diverse sources, including the human ES cells and the human iPS cells, as the technology for generating such cells from these sources is currently being developed [93,94]. The use of such cells would also prevent the dependency on human fetal derived cells, which are difficult to obtain in sufficient quantities required for grafting, and their use is also restrained because of ethical concerns [25].…”
Section: Discussionmentioning
confidence: 99%
“…A number of stem and progenitor cell types have been proposed for the treatment of neurological diseases including neural, bone marrow, umbilical cord, and embryonic stem cells (29,30). Many of these approaches have been used successfully in animal models to ameliorate degenerative conditions such as Alzheimer's (31, 32), Parkinson's (33,34), and Huntington's (35) disease, as well as other disorders such as epilepsy (36)(37)(38), excitotoxic brain damage (39), and traumatic brain injury (40). While a recent laboratory study has demonstrated the efficacy of transplanting salivary stem cells to alleviate radiation-induced xerostomia (41), with the exception of the bone marrow, the application of stem cell therapies to reduce radiation-induced normal tissue damage is still in its infancy.…”
mentioning
confidence: 99%
“…However, advances in stem cell technology are encouraging the idea that some regeneration of the central nervous system (CNS) is attainable. Embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) show tremendous promise for repairing the damaged brain in epilepsy (Carpentino et al, 2008;Maisano et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, advances in stem cell technology are encouraging the idea that some regeneration of the central nervous system (CNS) is attainable. Embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) show tremendous promise for repairing the damaged brain in epilepsy (Carpentino et al, 2008;Maisano et al, 2009).Stem cells are self-renewing and retain the potential to generate the three major CNS cell types-neurons, astrocytes, and oligodendrocytes. The brain's endogenous stem cells show limited capacity to replace injured or defective cell types.…”
mentioning
confidence: 99%